Bamboo-charcoal-loaded graphitic carbon nitride for photocatalytic hydrogen evolution. (19th January 2022) - Lu, Yongfeng; Wang, Wensong; Cheng, Hongrui; Qiu, Haijiang; Sun, Wenhao; Fang, Xiao; Zhu, Jiefang; Zheng, Yuanhui
Abstract: Crystalline graphitic carbon nitride is an excellent photocatalyst for hydrogen production due to its non-toxicity, stability, elemental abundance, and visible-light response. Herein, we present a new type of composite photocatalysts, eco-friendly bamboo-charcoal-loaded graphitic carbon nitrides to accelerate the separation of electron-hole pairs. The suitable loading of bamboo charcoal on graphitic carbon nitrides shows an increased specific surface area from 85 to 120 m 2  g −1, and excellent visible-light photocatalytic hydrogen production activity of 4.1 mmol g −1  h −1, which is 2.3 times higher than that of pristine carbon nitride (1.8 mmol g −1  h −1 ). Under irradiation, the photogenerated electrons fast migrate from graphitic carbon nitride to bamboo charcoal through an ohmic contact between them, reducing the recombination of electron-hole pairs. This study highlights the effect of carbonaceous material loading on photocatalytic activity of carbon nitrides and opens an avenue to design efficient loaded photocatalysts with natural abundant materials. Highlights: BC is loaded on g-C3 N4 via a simple method for visible-light driven H2 production. The modification of g-C3 N4 with nature-abundant materials is demonstrated. An ohmic junction between BC and g-C3 N4 accelerates the transfer of electrons.